The trade, debt and finance nexus: at the cross-roads of micro- and macroeconomics - Marc Auboin (World Trade Organization (WTO), 2004)
Trade liberalization is only one facet of the opening up of developing countries to the global economy. After a couple of decades of financial deregulation, liberalization of private capital movement and accumulation of debt at the international level, developing countries are raising issues of, if not incompatibility, at least sequencing and timing of the process of liberalization of capital movements and the process of liberalization of trade in goods and services. The consequences of the liberalization of both financial and "real" transactions is of increasing concern, particularly in emerging economies (i.e. successful integrators in the world economy), after a succession of financial crises in the 1990s (from Mexico to Asia, and some countries in South America), and with severe spill-over effects on growth and trade. Also, poor and very indebted countries face difficulties to integrate into world trade due to a lack of access to private capital markets, debt overhang, and deterioration in the terms of trade. The relationship between trade, debt and finance is equally important for them, and is part of the holistic policy environment which leads to development. This paper seeks to provide some clarification of this multi-faceted and complex relationship, and how the WTO is part of a national and international effort to address some of the challenges raised by these relationships. The paper reviews some of the theoretical links and existing literature on the subject, and analyses practical steps and priorities that are directly addressed in the newly established Working Group on Trade, Debt and Finance of the WTO. Finally, the paper addresses the issue of Coherence in the work of international organizations on some of the links highlighted in the first section.
Keywords: 330; trade and finance